2021
DOI: 10.1111/nan.12747
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mitochondrial and inflammatory homeostasis through RIP140 is neuroprotective in an adrenoleukodystrophy mouse model

Abstract: Aims Mitochondrial dysfunction and inflammation are at the core of axonal degeneration in several multifactorial neurodegenerative diseases, including multiple sclerosis, Alzheimer's disease, and Parkinson's disease. The transcriptional coregulator RIP140/NRIP1 (receptor‐interacting protein 140) modulates these functions in liver and adipose tissue, but its role in the nervous system remains unexplored. Here, we investigated the impact of RIP140 in the Abcd1− mouse model of X‐linked adrenoleukodystrophy (X‐ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…It negatively regulates energy homeostasis and positively regulates inflammatory response in macrophages, by indirect interaction between Nuclear Factor Kappa B ( NF- κ B ) and TLR -induced proinflammatory cytokines. Depletion of this gene was observed in the interruption of axonal degeneration (Ranea-Robles et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It negatively regulates energy homeostasis and positively regulates inflammatory response in macrophages, by indirect interaction between Nuclear Factor Kappa B ( NF- κ B ) and TLR -induced proinflammatory cytokines. Depletion of this gene was observed in the interruption of axonal degeneration (Ranea-Robles et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that RIP140 was upregulated in specific tissues that affected cerebral white matter in patients with CALD and spinal cord in ABCD1 mouse models, which may be due to the redox imbalance and excessive ROS required for RIP140 induction. Genic-silenced RIP140 restored mitochondrial function and redox homeostasis and prevented inflammatory response in X-ALD mouse models (36). Thus, inhibition of RIP140 may be regarded as a potential therapeutic target for X-ALD.…”
Section: Other Potential Targets Regulate Redox and Inflammation In X...mentioning
confidence: 96%
“…The exact cause of the onset and damage caused by oxidative stress and inflammation in X-ALD was unknown. However multiple in vivo/in vitro studies have demonstrated that drugs targeting redox imbalance and inflammation effectively improve symptoms and prevent disease progression (8,(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the tumor necrosis factor (TNF) superfamily, such as TNF-like weak inducer of apoptosis (TWEAK) and TNF-α, reduce the expression of PGC-1α and mitochondrial biogenesis by activating nuclear factor-κB (NF-κB) [ 52 ]. Interestingly, research has indicated that the absence of receptor-interacting protein 140 significantly increases mitochondrial biogenesis and intracellular FAO [ 53 ]. The exploration of key targets regulating PGC-1α is becoming increasingly important in the study of mitochondrial biogenesis.…”
Section: Molecular Regulations Of Mqcmentioning
confidence: 99%